Educação e religião: entrelaçamentos e influências na vida das pessoas transexuais. - Melo, Ana Margareth Manique de (2020)
This study sought to understand transgender people from access to formal education and their Christian, Catholic and evangelical religious experiences. It analyzed the possible forms of contribution of these markers to the intra and interpersonal relations of these people in contemporary times. Since the mid-1970s, a significant number of researchers have dedicated themselves to understanding human beings through sexuality. However, the vast majority are studies aimed at homosexuality and not transsexuality. Content such as education, religiosity, sexual repression, bio-power and social exclusion, related to the concepts of sex, sexuality, sexual orientation, gender identity and transsexuality were worked on. The qualitative methodology supported the semi-structured interviews, carried out with ten transsexual men and women aged between twenty-one and fifty-five years old, with different levels of education, living in the Greater Recife region. With this sample, we sought to achieve a plurality of experiences. Various forms of difficulties faced by transsexual people were pointed out, mainly, in family, religious, educational and labor market spaces, such as prejudice, discrimination, invisibility and exclusion. From the Discourse Analysis applied to the data obtained from the interviews, it was found that, to a large extent, formal education was a marker capable of influencing them in the choice of belonging to a religion, besides that, for these people, that is a legitimate way and capable of strengthening them to face the unpleasantness experienced in the search for respect and the conquest of citizenship, because as transsexuals they suffer because they are not framed in heteronormativity.